Answer:

**Answer:**

**12.5%**

**Step-by-step explanation:**

125 is 12.5% of 1000

Use the data set to create a quadratic function if it applies. Use the model to predict the value of x when y = -4. (-3, 10), (0, 4), (3, -1), (6, -5), (9, -8)Question 3 options:A) 29.32 and 3.97B) 32.27 and 4.57C) 27.48 and 5.20D) No Solution

6(5 + 3x) is equivalent too

All possible random samples of 200 middle managers are selected from a population for a study concerning their mean annual income. The population standard deviation is computed to be $2,248.5. What is the standard deviation of the sampling distribution of the means?

John has taken out a loan for college. He started paying off the loan with a first payment of $100. Each month he pays, he wants to pay back 1.1 times as the amount he paid the month betore. Explain to Jo howto represent his first 20 payment n sigma notation.Then esplain how to tind the sum of his frst 20 pyments, using complete sentences. Esplain why this series is convergent or divergent

Points F (0,0), G (9,0), and H (9,12) are the vertices of a triangle.What is the distance from point F to point H?A. 9B. 12C. 15D. 21

6(5 + 3x) is equivalent too

All possible random samples of 200 middle managers are selected from a population for a study concerning their mean annual income. The population standard deviation is computed to be $2,248.5. What is the standard deviation of the sampling distribution of the means?

John has taken out a loan for college. He started paying off the loan with a first payment of $100. Each month he pays, he wants to pay back 1.1 times as the amount he paid the month betore. Explain to Jo howto represent his first 20 payment n sigma notation.Then esplain how to tind the sum of his frst 20 pyments, using complete sentences. Esplain why this series is convergent or divergent

Points F (0,0), G (9,0), and H (9,12) are the vertices of a triangle.What is the distance from point F to point H?A. 9B. 12C. 15D. 21

**Hey There!**

__Answer:__

__HCF__**= 9**(*With the two numbers)***- 18,9****LCM = 3***(with the two numbers)**- 6,9*

**Step-by-step explanation:**

__HCF __

*If HCF is ''**9**''**that means that ''9'' is the divisible of two numbers.*

*So 18 and 19 can be divided by 9 and that's the highest divisible for both factors.*

*And always remeber the answer is a ''Prime factor.''*

__LCM__

*If LCM is ''**3**'' that means ''3'' is the lowest common multiple out of two numbers.*

**Hope this helps!**

**Have a nice Day!:)**

Plz I need help

**Answer:**

x= 116/17

**Step-by-step explanation:**

5x+192−321+13=−12x

Step 1: Simplify both sides of the equation.

5x+192−321+13=−12x

5x+192+−321+13=−12x

(5x)+(192+−321+13)=−12x(Combine Like Terms)

5x+−116=−12x

5x−116=−12x

Step 2: Add 12x to both sides.

5x−116+12x=−12x+12x

17x−116=0

Step 3: Add 116 to both sides.

17x−116+116=0+116

17x=116

Step 4: Divide both sides by 17.

17x/17=116/17

x = 116/17

About 2.1 cases so it maybe 2 full cases. Hope this helped!

sin(α) = ⁻⁵/₁₃

sin⁻¹[sin(α)] = sin⁻¹(⁻⁵/₁₃)

α ≈ 1.1256π

cos(β) = ²/₅

cos⁻¹[cos(β)] = cos⁻¹(²/₅)

β ≈ 1.6311π

sin(α - β) = sin(1.1256π - 1.6311π)

sin(α - β) = sin(-0.5055π)

sin(α - β) = -sin(0.5055π)

sin(α - β) = -sin(90.99)

sin(α - β) ≈ -0.116

sin⁻¹[sin(α)] = sin⁻¹(⁻⁵/₁₃)

α ≈ 1.1256π

cos(β) = ²/₅

cos⁻¹[cos(β)] = cos⁻¹(²/₅)

β ≈ 1.6311π

sin(α - β) = sin(1.1256π - 1.6311π)

sin(α - β) = sin(-0.5055π)

sin(α - β) = -sin(0.5055π)

sin(α - β) = -sin(90.99)

sin(α - β) ≈ -0.116

**Answer:**

1/12

**Step-by-step explanation:**

1/6 * 3/6 (First roll has a one in 6 chance, second 3 in 6)

1*3 / 36 =

3 / 36 =

1/12

Equation B: 3x + 2z = 1

Which of the following is a possible step used in eliminating the z-term?

Multiply equation A by −2.

Multiply equation B by 2.

Multiply equation A by 3.

Multiply equation B by 3.

a possible step used in eliminating the z-term is "multiply equation A by −2."

x + z = 6

3x + 2z = 1

x + z = 6 / *(-2)

3x + 2z = 1

-2x - 2z = -12

3x+ 2z = 1

-2x + 3x -2z +2z = -12 +1

x = -11

-11 + z = 6

z = 6 + 11

z = 17

x + z = 6

3x + 2z = 1

x + z = 6 / *(-2)

3x + 2z = 1

-2x - 2z = -12

3x+ 2z = 1

-2x + 3x -2z +2z = -12 +1

x = -11

-11 + z = 6

z = 6 + 11

z = 17

Answer:Multiply equation A by -2 is correct everyone

Step-by-step explanation:

I just took the test and checked;)